Dependence of n-butane activation on active site of vanadium phosphate catalysts - Yap, Taufiq Yun Hin; Goh, Chee Keong; Hutchings, Graham John; Dummer, Nicholas F.; Bartley, Jonathan K. (Springer, 2009)
The nature and the role of oxygen species and vanadium oxidation states on the activation of n-butane for selective oxidation to maleic anhydride were investigated. Bi–Fe doped and undoped vanadium phosphate catalysts were used a model catalyst. XRD revealed that Bi–Fe mixture dopants led to formation of αII-VOPO4 phase together with (VO)2P2O7 as a dominant phase when the materials were heated in n-butane/air to form the final catalysts. TPR analysis showed that the reduction behaviour of Bi–Fe doped catalysts was dominated by the reduction peak assigned to the reduction of V5+ species as compared to the undoped catalyst, which gave the reduction of V4+ as the major feature. An excess of the oxygen species (O2−) associated with V5+ in Bi–Fe doped catalysts improved the maleic anhydride selectivity but significantly lowering the rate of n-butane conversion. The reactive pairing of V4+-O− was shown to be the centre for n-butane activation. It is proposed that the availability and appearance of active oxygen species (O−) on the surface of vanadium phosphate catalyst is the rate determining step of the overall reaction.